Pengembangan Bahan Ajar Etnomatematika Mengunakan Model RME Materi Pecahan untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 13 Tambun Sungkean: Penelitian - Insa Gultom; Ahmad Landong (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The research conducted aims to develop ethnomathematics teaching materials using the RME model to improve the learning outcomes of fourth grade students of SDN 13 Tambun Sungkean and to determine the validity, practicality and effectiveness of the developed teaching materials. In this study, the researcher used the ADDIE development procedure consisting of 5 stages. The instrument used to determine the validity, practicality and effectiveness of ethnomathematics teaching materials using the RME model to improve the learning outcomes of fourth grade students of SDN 13 Tambun Sungkean, namely a questionnaire. The validity of ethnomathematics teaching materials using the RME model of fraction material developed obtained a percentage of 90% with the criteria of "Very Valid" from the expert validator of teaching materials and obtained a percentage of 92.94% with the criteria of "Very Valid" from the expert validator of material. The practicality of the developed teaching materials was validated by the fourth grade teacher of SDN 13 Tambun Sungkean. From the validation carried out, the maximum percentage was obtained, namely 100% with the category of "Very Practical". The effectiveness of ethnomathematics teaching materials using the RME model of fraction material developed was assessed using a student response questionnaire. From the validation, a percentage of 100% was obtained with the criteria "Very effective".